A Tinjauan Pelaksanaan Sistem Penomoran Rekam Medis Rawat Jalan di Puskesmas Tambarangan Kabupaten Tapin - Nilna Hidayah; Faizah Wardhina; Purwanto Purwanto (HB PRESS, 2021)
The numbering system in the medical record service is the procedure for writing given to the patients when they come for treatment as a part of their identity. This study aimed to describe the implementation of the outpatient medical record numbering system at the Tambarangan Public Health Center in Tapin Regency. This research used a descriptive method. The study results included the family numbering system consisting of five digits medical record number, i.e., the first two digits were based on the village area code while the last three digits were the medical record number. The advantages of the family numbering system were that it was faster in finding medical record files of the family members and the convenience to save medical record storage space and budget. Meanwhile, the shortcomings of the family numbering system were that it took a long time if the patient did not come for treatment for a long time and slowed down and hindered service if the patient did not carry an identity card for treatment and forgot his medical record number. The constraints in implementing the numbering system based on the man element were no medical record officer with the qualification of Diploma Medical Record and Health Information, and the officer never attended training/technical guidance/socialization regarding the medical record numbering system. The constraints based on the machine were the availability of only one computer that was only used for checking social health insurance. The constraints regarding the methods were no standard operating procedures found regarding the medical record numbering system, and the public health center management information system was no longer used because its implementation was constrained by non-existent technical personnel. The constraints regarding the materials were the patient's main index card that was not used, and the time to provide outpatient medical records was less than 10 minutes.